Global diversity and distribution of close relatives of apicomplexan parasites. (1st June 2018) - Mathur, Varsha; del Campo, Javier; Kolisko, Martin; Keeling, Patrick J.
Summary: Apicomplexans are a group of obligate intracellular parasites, but their retention of a relict non‐photosynthetic plastid reveals that they evolved from free‐living photosynthetic ancestors. The closest relatives of apicomplexans include photosynthetic chromerid algae (e.g., Chromera and Vitrella ), non‐photosynthetic colpodellid predators (e.g., Colpodella ) and several environmental clades collectively called Apicomplexan‐Related Lineages (ARLs). Here we investigate the global distribution and inferred ecology of the ARLs by expansively searching for apicomplexan‐related plastid small ribosomal subunit (SSU) genes in large‐scale high‐throughput bacterial amplicon surveys. Searching more than 220 million sequences from 224 geographical sites worldwide revealed 94 324 ARL plastid SSU sequences. Meta‐analyses confirm that all ARLs are coral reef associated and not to marine environments generally, but only a subset is actually associated with coral itself. Most unexpectedly, Chromera was found exclusively in coral biogenous sediments, and not within coral tissue, indicating that it is not a coral symbiont, as typically thought. In contrast, ARL‐V is the most diverse, geographically widespread and abundant of all ARL clades and is strictly associated with coral tissue and mucus. ARL‐V was found in 19 coral species in reefs, including azooxanthellate corals at depths greater than 500 m. We suggest this is indicative of a parasitic or commensal relationship, and not of photosynthetic symbiosis, further underscoring the importance of isolating ARL‐V and determining its relationship with the coral host.